An Ecosystem‐Level Process Model of Business Model Disruption: The Disruptor's Gambit - Snihur, Yuliya; Thomas, Llewellyn D. W.; Burgelman, Robert A. (Journal of Management Studies, 2018)
Based on a longitudinal case study, this paper presents an ecosystem‐level process model of the interlocking key activities of the business model disruptor, other ecosystem participants (customers, partners, media, analysts), and the incumbent. Together these constitute a strategic process of ecosystem evolution from incumbent‐centred to disruptor‐centred. We identify the phenomenon of a ‘disruptor's gambit’, where the disruptor reveals its intentions early on through effective framing, followed by rapid adaptation of its business model to satisfy ecosystem needs. These processes generate a virtuous framing‐adaptation cycle, where feed‐forward and feedback enable rapid response to customers and partners, while engaging them as force multipliers during new ecosystem creation. Our findings suggest that framing constitutes a dynamic strategic process enabling disruptors to reduce uncertainty, dislodge powerful incumbents, and shape new ecosystems through business model innovation.